Medical Error and Resident Training - Soto, Mauricio Andres (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2013)
Errors in medicine occur in all contexts in which it can be developed. For instance, in pre and post-graduate education, where the subsequent analyses that are helping to conceptualize and develop medical professionalism. This is why postgraduate education makes it necessary for residents to develop a serious attitude towards their formative process, allowing them to understand the importance of a quality education. In this regard, supervising physicians should not forget to respect residents’ autonomy and learning curve. It is also important to take into account the family-social and labor-educational environments, potentially incompatible, and often resulting in sleep deprivation, lack of free time, burnout, and depression.